FAKTOR YANG MEMPENGARUHI KEPUTUSAN PETANI MEMILIH PADI VARIETAS INPARI 15 DI KELURAHAN WAWONGGOLE KECAMATAN UNAHAA KABUPATEN KONAWE - Leni Saleh; Endang Sumiratin (JAS (Jurnal Agri Sains), 2023)
This study aims to analyze what factors influence farmers' decisions in selecting Inpari 15 rice varieties in the Wawonggole Village, Unaaha District, Konawe Regency. Respondents who were taken in this study were 24 farmers who planted seeds of the Inpaer 15 variety in the Wawonggole Village, Unaaha District. The variables used in this study were the dependent variable (the farmer's decision to apply the Inpari 15 rice variety) and the independent variables (individual, production, land, and environment). Based on the results of the study, it showed that individual factors (X1), production factors (X2), land factors (X3) and environmental factors (X4) in their tests had an influence on farmers' decisions (Y) in selecting Inpari 15 variety seeds. The significance value met the criteria that farmers in making decisions to use seeds of the Inpari 15 variety, at the 95% level of confidence or error α = 0.05.